Pemberdayaan Guru Sekolah Dasar Gugus II Kecamatan Gerung dalam Mengimplementasikan Alat Peraga Kopermatik - Sri Subarinah; Tabita Wahyu Triutami; Sudi Prayitno; Junaidi Junaidi; Dwi Novitasari (Rengganis Jurnal Pengabdian Masyarakat, 2022)
Elementary school teachers in Cluster II of the Gerung sub-district are very rare and some have never even used teaching aids in teaching mathematical concepts. That makes students have difficulty understanding abstract mathematics subject matter, while elementary school children are still in the stage of concrete or semi-abstract thinking. Therefore, this activity aims to empower elementary school teachers in Cluster II of the Gerung sub-district in implementing Kopermatik teaching aids (Math Game Box) by providing training to elementary school teachers on how to make and use Kopermatic props. Kopermatik is a set of elementary school mathematics teaching props that include teaching aids for learning algebra, geometry, and numbers. The training methods include (1) presentation of material, (2) demonstration, (3) making of teaching aids in groups, (4) presentation of group work results, and (5) evaluation and follow-up. The service activity was located at SDN 2 Dasan Geres, with 18 elementary school teachers as participants. all participants actively practice making props for number cards and fraction cards in groups of two. The results of this activity are : (1) all participants practice making props for number cards and fraction cards in groups of two, and (2) 95% of participants can demonstrate the props they made correctly. The results of the questionnaire showed that all participants were happy with this activity and hoped that it would be held again for a longer time and with more materials. Participants can understand the training material because it is interesting and easy to understand